2010
DOI: 10.1111/j.1365-2265.2010.03880.x
|View full text |Cite
|
Sign up to set email alerts
|

Macroprolactinaemia in patients with hyperprolactinaemia: composition of macroprolactin and stability during long‐term follow‐up

Abstract: This study showed that higher PEG-precipitable PRL ratio in macroprolactinaemic sera might preferentially indicate the presence of anti-PRL autoantibodies and that macroprolactinaemia might be a long-lasting condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 28 publications
3
29
0
Order By: Relevance
“…However, further, more comprehensive serial investigations of patients with macroprolactinemia reported a mild symptomatology with a lower incidence of clinical symptoms and abnormal imaging findings in the pituitarry gland than in patients with true hyperprolactinemia [3,5,10,15,[19][20][21][22]. During prolonged follow-up of a cohort of 51 patients with macroprolactinemia headache had been experienced in 12 patients (24%), oligomenorrhea in five (10%) and galactorrhea was present in only two cases (4%) with no symptomatic progression in any of the patients [5].…”
Section: Clinical Featuresmentioning
confidence: 98%
See 4 more Smart Citations
“…However, further, more comprehensive serial investigations of patients with macroprolactinemia reported a mild symptomatology with a lower incidence of clinical symptoms and abnormal imaging findings in the pituitarry gland than in patients with true hyperprolactinemia [3,5,10,15,[19][20][21][22]. During prolonged follow-up of a cohort of 51 patients with macroprolactinemia headache had been experienced in 12 patients (24%), oligomenorrhea in five (10%) and galactorrhea was present in only two cases (4%) with no symptomatic progression in any of the patients [5].…”
Section: Clinical Featuresmentioning
confidence: 98%
“…However, macroprolactinemia may be more common, with a recently reported prevalence of 3.7% and no difference in prevalence between genders [14]. Because the reported proportion of macroprolactinemia in hyperprolactinemic populations is much higher in most studies and varies between 15 and 35% (mean prevalence 25%), macroprolactinemia is therefore considered a common finding in endocrinological practice [3,8,12,13]. One study reported a prevalence of 46%, but it is likely that this particular incidence reflected selection bias because of the specialized nature of the study center, which received samples sent from other laboratories when the possible diagnosis of macroprolactinemia was raised [15].…”
Section: Prevalencementioning
confidence: 98%
See 3 more Smart Citations